2022
DOI: 10.1021/acs.nanolett.2c02019
|View full text |Cite
|
Sign up to set email alerts
|

Locking and Unlocking Thrombin Function Using Immunoquiescent Nucleic Acid Nanoparticles with Regulated Retention In Vivo

Abstract: The unbalanced coagulation of blood is a lifethreatening event that requires accurate and timely treatment. We introduce a user-friendly biomolecular platform based on modular RNA-DNA anticoagulant fibers programmed for reversible extracellular communication with thrombin and subsequent control of anticoagulation via a "kill-switch" mechanism that restores hemostasis. To demonstrate the potential of this reconfigurable technology, we designed and tested a set of anticoagulant fibers that carry different thromb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…Furthermore, in the absence of a carrier, NANPs are essentially invisible to cells and so are immunoquiescent ( 104 106 ). This makes them perfect candidates for extracellular use ( 107 ). Cationic lipids and liposomes have been extensively explored as carriers for TNAs and can also serve as viable carrier options for NANPs.…”
Section: Combinations Of Different Carriers and Nanps As Intracellula...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in the absence of a carrier, NANPs are essentially invisible to cells and so are immunoquiescent ( 104 106 ). This makes them perfect candidates for extracellular use ( 107 ). Cationic lipids and liposomes have been extensively explored as carriers for TNAs and can also serve as viable carrier options for NANPs.…”
Section: Combinations Of Different Carriers and Nanps As Intracellula...mentioning
confidence: 99%
“…Previous work has shown trends in the degree of immune response based on the previously mentioned design features ( 106 ) ( 101 ). Differences in dimensionality (1D, 2D, and 3D), composition (DNA or RNA), and connectivity (intramolecular, intermolecular, or both) evoke varying immune responses and enable NANPs to be customized based on the intended therapeutic effect ( 107 ). The field of therapeutic nucleic acids continues to advance and holds the promise of the development of versatile new means to manipulate host cell machinery to achieve a desired therapeutic effect in the absence of detrimental recipient responses ( 120 , 121 ).…”
Section: Combinations Of Different Carriers and Nanps As Intracellula...mentioning
confidence: 99%
“…Strand displacement is a reaction between DNA or RNA strands that is essential to dynamic nucleic acid nanotechnology, and has been used in nucleic acid circuits designed for molecular computing, as well as in synthetic biology and molecular sensing [183] . Furthermore, there is increasingly more evidence that strand displacement is also involved in numerous naturally occurring processes, such as during RNA cotranscriptional folding or during RNA invasion into double-stranded DNA in the CRISPR-Cas9 complex [184] .…”
Section: Research Highlightsmentioning
confidence: 99%
“…For instance, fibrous materials offer a large surface area, allowing the delivery of a more significant number of functional moieties than a spherical nanocarrier may offer. Moreover, a nonspherical shape has been suggested to improve the vascular transport of nanomaterials and therapeutic cargo delivery into the interstitial space. , To leverage these benefits of fibrous shape while avoiding undesirable inflammatory responses, researchers turned their attention to “soft” and biodegradable materials such as those made of natural RNA and DNA biopolymers. The field of nucleic acid nanoparticles (NANPs) is fast growing and has already demonstrated numerous beneficial, safe, and environmentally friendly applications ranging from therapeutic indications as nanomedicines to the use as structural components of light-emitting diodes, functional photonic devices, and biosensors. …”
mentioning
confidence: 99%
“…This property enables the extracellular use of NANPs, particularly in cases in which inflammation is undesirable, such as in blood anticoagulation. A recent study demonstrated the successful use of RNA/DNA fibers functionalized with thrombin aptamers and their respective “kill switches” to control blood clotting . In extensive work combining in vitro human-blood-based assays and in vivo studies in small (i.e., mice) and large (i.e., pigs) animals, the anticoagulant NANPs were effective and well-tolerated.…”
mentioning
confidence: 99%